“When I need help, I ask my friends”: experiences of Spanish autistic women when disclosing their late diagnosis to family and friends - Garcia-Molina, Irene (Frontiers in Psychology, 2024)
Family and friends may play an important role both in the identification and diagnosis of any condition, as well as in the provision of support afterwards. However, when the diagnosis is autism and it arrives late, as is often the case with autistic women, we find the double stigma of experiencing the repercussions of a late diagnosis, along with the disbelief of those closest to them. This study aims to analyse and understand the experiences of autistic women with their family and friends throughout the diagnostic process and subsequent help-seeking endeavors. A total of 21 Spanish autistic women aged between 20 and 58 years answered a series of open-ended questions—respecting the participants' preferred modality. From the thematic analysis, two main themes emerged regarding the reactions of family and friends, dividing the experiences into two temporal phases: when disclosing the diagnosis and sometime later. Most participants noted that their relatives did not believe them, reacted in a hostile way, or did not give it any importance at the time of disclosure. As a result, their relationship deteriorated even further over time. In contrast, their friends served as pillars of support from the beginning, along with their partners and the associations they attended, because of which they met more autistic women who became their “family”. Thus, another consequence of late diagnosis in autistic women is highlighted, the incomprehension or disbelief from their relatives, and the important role of friendships among women and among autistic women.